ECE302HW3Soln_Sp10

ECE302HW3Soln_Sp10 - ECE 302: Homework 3 Prof. Saul Gelfand...

Info iconThis preview shows pages 1–4. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ECE 302: Homework 3 Prof. Saul Gelfand Spring 2010 Due February 19, 2010 Problem 1 a. First we find the constant c by noting that integraldisplay ∞ −∞ f X ( x ) dx = integraldisplay ∞ − 1 ce − 2 x dx = c 2 e 2 = 1 . Therefore c = 2 e − 2 and f X ( x ) = 2 e − 2 x − 2 . Now since Y = X 2 ⇒ X = √ Y , we compute We then have that the CDF F Y ( y ) = Pr [ Y < y ] = Pr [ X 2 < y ] = Pr [- √ y < X < √ y ] for the case that y < 1, we have F Y ( y ) = Pr [- √ y < X < √ y ] = integraldisplay √ y − √ y f X ( x ) dx = integraldisplay √ y − √ y 2 e − 2 x − 2 dx = e 2 √ y − 2- e − 2 √ y − 2 . For the case that y ≥ 1, we have F Y ( y ) = Pr [- 1 < X < √ y ] = integraldisplay √ y − 1 f X ( x ) dx = integraldisplay √ y − 1 2 e − 2 x − 2 dx = 1- e − 2 √ y − 2 . 1 Therefore F Y ( y ) = braceleftbigg e 2 √ y − 2- e − 2 √ y − 2 , < y < 1 1- e − 2 √ y − 2 , y ≥ 1 ⇒ f Y ( y ) = d dy F Y ( y ) = , y ≤ exp(2 √ y − 2) √ y + exp( − 2 √ y − 2) √ y , < y < 1 exp( − 2 √ y − 2) √ y , y ≥ 1 We find Pr [ Y > 2 X ] = Pr [ X 2 > 2 X ] = Pr [ X > 2] as an integral of the PDF f X ( x ) as follows Pr [ X > 2] = integraldisplay ∞ 2 f X ( x ) dx = integraldisplay ∞ 2 2 e − 2 x dx = e − 4 b. We again find c by noting ∞ summationdisplay i = −∞ p X ( x i ) = ∞ summationdisplay x i = − 1 c parenleftbigg 1 2 parenrightbigg x i +1 = 1 ⇒ (let k = x i + 1) ∞ summationdisplay k =0 c parenleftbigg 1 2 parenrightbigg k = 2 c = 1 , so that c = 1 2 and p X ( x i ) = ( 1 2 ) x i +2 . We then have that p Y ( y ) = Pr [ Y = y ] = Pr [ X 2 = y ] We have that for y = 1, there are two values of X ( X = 1 ,- 1) such that X 2 = y = 1. Therefore p Y (1) = Pr [ Y = 1] = Pr [ X = 1] + Pr [ X =- 1] = p X (1) + p X (- 1) = parenleftbigg 1 2 parenrightbigg 3 + parenleftbigg 1 2 parenrightbigg = 5 8 . For all other values of X = 0 , 2 , 3 , 4 , . . . , we have only one value of Y which is mapped to, therefore p Y ( y ) = Pr [ X 2 = y ] = Pr [ X = √ y ] = p X ( √ y ) = parenleftbigg 1 2 parenrightbigg √ y +2 , for y = 0 , √ 2 , √ 3 , . . . . 2-b-a a b-b b X Y = g(X) Figure 1: Problem 2 Problem 2 We have the limiter function Y = g ( X ) plotted as shown in Figure 1. We let a = 1 and b = 2 in this problem....
View Full Document

This note was uploaded on 02/07/2011 for the course ECE 302 taught by Professor Gelfand during the Fall '08 term at Purdue.

Page1 / 10

ECE302HW3Soln_Sp10 - ECE 302: Homework 3 Prof. Saul Gelfand...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online